Predicting Mortality in Elderly Patients with Hypertensive Crises: Development and Validation of a Risk Model - Erkan Boga (Albanian Journal of Trauma and Emergency Surgery, 2025)
Introduction: Hypertensive crises, which are marked by severe increases in blood pressure with or without acute target organ damage, represent a critical condition associated with substantial morbidity and mortality, particularly among older adults. As global life expectancy increases, the prevalence of hypertension and its complications also rises, creating an urgent need for effective strategies for early risk assessment and intervention. This study aims to develop and validate a risk model for predicting mortality in elderly patients experiencing hypertensive crises. Given the high morbidity and mortality rates associated with hypertensive crises in this population, an accurate risk assessment tool could enhance clinical decision-making and improve patient outcomes.